Edukasi dan Pendampingan Pembuatan Ovitrap sebagai Upaya Pengendalian Demam Berdarah - Suryadi, Iwan; Lestari, Virny Dwiya; Widyatuti, Nugraheni; Fitriani, Nurlaila (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2023)
Dengue Hemorrhagic Fever (DHF) or Dengue Haemorhagic Fever (DHF) is one of several infectious diseases that are a health problem in the world, especially developing countries. Aedes spp mosquitoes are vectors of arbovirus diseases, including Yellow Fever, Dengue Fever, Dengue Hemorrhagic Fever (DHF), and Chikungunya. One method of controlling Aedes is the use of ovitrap. This service aims to provide education and assistance in the manufacture of ovitrap as one of the efforts to control DHF. This service is carried out by providing knowledge about dengue disease and its control and how to make simple ovitrap. Education is carried out by means of counseling which was previously given a pre-test and post-test as a measuring tool for increasing knowledge. The standard ovitrap is made with a small wide-mouthed glass/pot painted black on the outside and given gauze as an egg trap. The glass is half filled with water to part and placed inside and outside the house which is suspected to be the habitat of the Aedes mosquito. The results of education and assistance in making ovitrap for cadres in the Tamangapa sub-district were that participants benefited, namely increasing knowledge and increasing skills in making ovitrap. The conclusion of this activity is that the community gets an increase in general knowledge about DHF, Aedes Aegypty mosquitoes and how to control them and increases skills in making ovitrap